The Arte da grammatica da Lingoa mais vsada na costa do Brasil and some epochal notes. - Fonseca, Maria do Céu (2012)
The years of 1997 and 1998 paid tribute to the first worshipper of poetry in Brazil. The University of Coimbra honoured the name of Anchieta with a commemorative international congress celebrating the 450 years over the inauguration of the Colégio das Artes . Some time before, another moment of high reflection had taken place in the city of São Paulo, during the international congress evocative of the 4th centenary of one of their founders’ death. In both congresses, illustrious personalities “congregated”– thus implies the meaning of “congress”– around the literary and linguistic work, the missionary and ethnographic endeavour, and other multiple facets of a figure of the Brazilian 16th century, who burst into history by the fifties with the fruits that we know.